A study on the problems and prospects of franchisors in operating their franchise business in Malaysia / Md. Tahir A. Hamid and Roaimah Omar - A. Hamid, Md. Tahir; Omar, Roaimah (2005)
This is an empirical study into the problems and prospects franchisors in operating their franchise businesses in Malaysia. This study has adopted an exploratory analytical approach by means of a personal interview involving selected franchisors in Malaysia. There are three objectives the study, Firstly it is to investigate empirically the various problems faced by the franchisors with their franchisees in running their franchise businesses. Secondly, it is to evaluate franchisors' satisfaction areas with their franchisees. Thirdly, it is to make some recommendation in order to encourage more Bumiputra to venture into this kind of business as franchisors. In general, the empirical results indicated that most of the franchisors are happy with the performances of their franchisees, although some have only minor problems with the franchisees in running their businesses. Overall, most of the franchisors are satisfied with their businesses. Most them are looking for new franchisees to expand their businesses. Bumiputra businessmen should take advantage of such business as franchisors. The Malaysian Government through the Ministry of Entreprenuer Development is providing many facilities to encourage more Bumiputras to get involved in this kind of business.